Assessing Pedagogical Competence Performance of Pre-Service Business Educators in North East, Nigeria - Bello, M.I.; Egunsola, A.O.E.; Awak, R.S. (Kashere Journal of Education, 2022)
The purpose of the study was to explore pedagogical competence performance of Pre-service Business Educators’ (PBEs) in North East, Nigeria. The design for the study was a descriptive survey design. The area for the study covered all Federal Universities of Technology in North East Nigeria offering Business Education courses. The population of the study stood at 1064, when split, 491, 491 and 82 are PBEs’, Cooperating Supervisors (CS) and University Supervisors (US) respectively. Stratified proportionate sampling technique was employed to arrive at 514 guided by Krejcie and Morgan table for determining sample size, which when split accounts for 216, 216 and 82 PBEs, CS and US respectively. One structured questionnaire, namely, Pedagogical Competence Performance Schedule Questionnaire (PCPSQ) used for data collection were adapted from three different authors. The PCPSQ contains 21, 21 and 18 items covering Instructional Design (ID), Classroom Management (CM) and Classroom Assessment Techniques (CAT) competences. Results obtained in the pilot tested questionnaire revealed Cronbach’s alpha of PCPSQ to be 0.89. Data collected were analyzed using SPSS (Version 25). The findings of the study among others revealed a significant difference among the triad in two out of the three clusters, consisting of CM and CAT. Based on the findings, the study recommended among others a synergy be created between Universities and Ministries of Education, where workshops and seminars are carried out to availed those that are directly involved in teaching practice the skills in CM and CAT competences.